SiPM-based camera for gamma-ray imaging air Cherenkov telescope. Issue 1 (1st November 2022) - Chernov, D.; Bonvech, E.; Astapov, I.; Bezyazeekov, P.; Borodin, A.; Brueckner, M.; Budnev, N.; Chernukh, D.; Chiavassa, A.; Dyachok, A.; Fedorov, O.; Gafarov, A.; et al.
Abstract : The current status of the equipment development for the new wide-angle gamma-ray imaging air Cherenkov telescope for TAIGA hybrid installation is presented. A front-end electronic and data acquisition system board based on the Zynq family Xilinx FPGA chips specially designed for this project have been produced and are being tested. A detailed description if presented for internal structure of the four main subsystems: four 8-channel 100 MHz ADCs, board's control system, internal clock and synchronization system and the power supply system. Additionally, the current status of a small scale prototype telescope SIT consisting of 49 SiPM is presented. The telescope includes a digital camera for observing the stars and weather condition. The SIT-HiSCORE synchronization systems and the telemetry information collection had been tested.